Desktop encyclopedia of telecommunications - Muller, Nathan J (McGraw-Hill telecommunications, 1998)
This comprehensive reference explains the telephone side of the telecommunications industry, and includes information about all of the latest developments, including wireless, the Web, signalling system #7, TCP/IP, video-conferencing and multimedia.